Fission yeast Rep2 is a putative transcriptional activator subunit for the cell cycle 'start' function of Res2-Cdc10. - Nakashima, N (1995)
In the yeast cell cycle 'start' requires sets of the Cdc10/ SWI family of transcriptional factors which activate the MCB cis elements contained in genes essential for S phase progression. Fission yeast possess two such overlapping systems, Res1-Cdc10 and Res2-Cdc10, both of which act to start the mitotic and meiotic cycles. We have recently isolated rep2+ as a multicopy suppressor of a temperature-sensitive cdc10 mutant which encodes a zinc finger protein. Here we show that the Rep2 zinc finger protein is an essential component of the active Res2-Cdc10 transcriptional regulator complex and likely to play a role in the control of cell cycle 'start'. Our data suggest that Rep2 is a transcriptional activator subunit which interacts with the MCB binding subunit complex formed by Res2 and Cdc10.